Narratives of TESOL professionals : experiences navigating the doctoral program - Kayi-Aydar, Hayriye; Steadman, Angel; Shea, Kate (ESL Instructor) (Contemporary perspectives on learning environments, 2023)
"Through insiders' perspectives and narratives, this edited collection provides insight into the lived experiences of recent graduates of various English Applied Linguistics and/or TESOL doctoral programs in North America. The authors document how their personal and professional identities intersected during their doctoral studies and how these doctoral programs, as learning environments, supported them in their professional development and dissertation research. As such, their insider perspectives and narratives are of special value to those contemplating pursuing such a program, or are in progress towards their own degree, as well as the faculty members who advise and support these doctoral students. Chapters focus on topics immediately relevant to success and persistence in a doctoral program, such as developing a network of mentors, establishing a work-life balance, and professional socialization, among others. All authors are recent graduates of their programs who have been intentionally selected for their recent memories in navigating the process. At a time when doctoral program persistence declines at the intersection of students' gender and racial background (see Okahana & Zhou, 2019) there is a pressing need to share the insights and lived experiences of those less commonly featured in narratives of the successful doctoral scholar. This need is especially true among TESOL professionals who will teach and learn in diverse, global settings throughout their careers following their graduation. This book contributes to that need, and it is an essential resource for scholars in TESOL/English Applied Linguistics and other similar doctoral programs"--